The Theology and Practice of the Jesus Prayer - Hendi (ADI Publisher, 2020)
This article explains the theology and practice of the Jesus Prayer. Prayer, to the average person, is asking God for something. But the Jesus prayer is not this. It is an attempt to change the one who prays. This prayer is traditionally a monastic prayer. Its simplicity allows everyone to practice it. In this prayer, there is faith and hope in the goodness of Christ. It is the prayer from our whole being. It is a cry out of the deep heart and nepsis without ceasing. The unceasing repetition of the Jesus Prayer kept the mind on the thought of God and dispersed all irrelevant thoughts (logismoi). This is the prayer requires watchfulness as a lantern requires a candle. Watchfulness, mature in Christ, the fruit of Spirit, and theosis will follow in the praying unceasingly: the Jesus Prayer.